Determinan Struktur Modal Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di Bei 2015 – 2019 - Saiful Anwar; Anita Wijayanti; Yuli Chomsatu (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to determine the factors that influence the company'scapital structure including: company age, profitability, net profit margin, sales stability, total asset turnover in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period. Sampling in this study used purposive sampling. The sample companies in this study amounted to 12 companies that met the sampling criteria. Technical analysis of the data used in this research is to use multiple linear analysis. The results of this study indicate that company age has no effect on capital structure, profitability has no effect on capital structure, net profit margin has no effect on capital structure, company stability has no effect on capital structure, total asset turnover has no effect on capital structure.